POLITENESS STRATGEIES USED BY ENGLISH TEACHERS IN TEACHING LEARNING PROCESS AT SECONDARY SCHOOL - M.S. Goray Sihombing; Fahri Haswani (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This study described politeness strategies used by the English teachers one of secondary school in Medan. The source of the data was two English teachers of class VIII and IX in one of the junior high school in Medan, Indonesia. This study was analyzed politeness strategies in the teaching learning process according Brown and Levinsons’ (1987). The data collection technique was video recording and interviewing.The findings were (1) there were four politeness strategies; Bald on Record 137 (47,08%), Positive Politeness 89 (30,58%), Negative Politeness 48 (16,49%), and Off Record 17 (5,84%). (2) Bald on Record was realized to make the close relationship between teachers and students. Positive Politeness strategies were realized to give respect to students. Negative Politeness was realized to maintain closer friends among them and Off Record was realized to give the students the opportunity to care for the teacher said.This study was referred Politeness, it is influenced by Power, Distance, and Relationship, and affected by speech events and politeness is the use of the right word in the power context, it is determined by the rules that are prevalent in society. The result was constributed teachers, linguists, other researcher sociolingustics lecturers and government that impicated with directly or indirectly involved to online learning as the classroom and the teaching learning process at school are suggested to apply this politeness strategies which put impact students’ attitude and behavior and to elaborated of politeness, politeness strategies, the reason of politeness strategies, E-Learning and Teacher and students communication.